The Pantanal (Brazil) - Biodiversity between drought and flooding - Wittmann, Florian Karl; Junk, Wolfgang Johannes (Geographische Rundschau, 2011)
With 160 000 km 2, the Pantanal is one of the world's largest inland wetlands. It is situated in a depression, which has been filled with sediments by the Paraguay River and its tributaries since Pliocene/Pleistocene times. Varying water discharge and sediment transport of the rivers during dry glacial and wet interglacial periods led to a small-scale mosaic surface relief. This results today in a large diversity of habitats, characterized by different length of inundation. The vegetation corresponds to the surrounding savanna (Cerrado) belt. But there are also species from other adjacent biomes, such as the Amazon rain forest, the Atlantic forest, and the Chaco. About 1.900 species of higher plants are described, of which about 750 species are woody species. About half of them colonize terrestrial habitats. Most of the others have a broad ecological amplitude and tolerate flood and drought stress.
Das Pantanal (Brasilien) -Artenreichtum zwischen dürre und vernässung
Keywords: Drought Stress; Flooding; Interglacial; Pliocene-pleistocene Boundary; Rainforest; River Discharge; Sediment Transport; Species Diversity; Amazonas; Argentina; Atlantic Forest; Bolivia; Chaco [argentina]; Pantanal; Paragua River; Santa Cruz [bolivia]; Embryophyta; Tracheophyta